Effect of Syzygium calophyllifolium Walp. seed extract on transaminases and phosphatases in alloxan induced diabetic rats - Gurusamy, K. (Medknow Publications & Media Pvt Ltd, 2007)
The antidiabetic effect of an aqueous seed extract of Syzygium calophyllifolium Walp. was studied in alloxan induced diabetic rats. Changes in serum and tissue AST, ALT LDH, ACP and ALP, enzymes activities in alloxan induced rats were studied and found to be reversed by the oral administration of S.calophyllifolium seed extract.